2015
DOI: 10.1371/journal.pone.0136389
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fishmeal Replacement in Diets for Gilthead Sea Bream (Sparus aurata) on the Gastrointestinal Microbiota Determined by Pyrosequencing the 16S rRNA Gene

Abstract: Recent studies have demonstrated the impact of diet on microbiota composition, but the essential need for the optimization of production rates and costs forces farms and aquaculture production to carry out continuous dietary tests. In order to understand the effect of total fishmeal replacement by vegetable-based feed in the sea bream (Sparus aurata), the microbial composition of the stomach, foregut, midgut and hindgut was analysed using high-throughput 16S rDNA sequencing, also considering parameters of grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
141
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(180 citation statements)
references
References 60 publications
32
141
1
1
Order By: Relevance
“…In particular, the intestinal inflammatory profile, the antioxidant activation, the imbalance of the genes involved in mucus production, the changes in the epithelial junctions, and the decrease in Rt were returned to the levels of control fish. Recent studies have shown that fish meal replacement also has an impact on fish microbial profile [63]. Thus, further studies are underway to determine the changes induced in the intestinal microbiome and the possible protection of fish against pathogen challenges with this additive.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the intestinal inflammatory profile, the antioxidant activation, the imbalance of the genes involved in mucus production, the changes in the epithelial junctions, and the decrease in Rt were returned to the levels of control fish. Recent studies have shown that fish meal replacement also has an impact on fish microbial profile [63]. Thus, further studies are underway to determine the changes induced in the intestinal microbiome and the possible protection of fish against pathogen challenges with this additive.…”
Section: Discussionmentioning
confidence: 99%
“…Singletons, or OTUs represented by only one sequence read, were removed from analysis. Clusters assigned to the order chloroplast or the family mitochondria were removed from analysis, as they represented reads derived from plant material found in the diets and eukaryotic and host mitochondrial DNA, respectively, and were not considered functional microbiota [47]. We further required OTUs to account for at least 0.0001% of the overall abundance, in order to reduce the incidence of spurious OTUs.…”
Section: Methodsmentioning
confidence: 99%
“…,b; Estruch et al . ; Schmidt et al . ), as concern over the use of fishmeal forces aquaculturists to test new, plant protein‐based formulations.…”
Section: Factors Influencing Fish Gut Microbiome Structurementioning
confidence: 99%
“…Diet is recognized as a primary factor influencing diversity and community structure of fish gut microbiomes. The majority of studies relating diet and microbiome composition alter diet treatments in culture or controlled settings (Desai et al 2012;Ingerslev et al 2014a,b;Estruch et al 2015;Schmidt et al 2016), as concern over the use of fishmeal forces aquaculturists to test new, plant protein-based formulations. As microbial communities play an important role in nutrient acquisition and provide a protective barrier against opportunistic pathogens (Llewellyn et al 2014), gut microbiome manipulation is often tested as a mechanism to increase feed efficiency, growth and disease resistance of fish in aquaculture (Dimitroglou et al 2011).…”
Section: Dietary Factorsmentioning
confidence: 99%